Living Sufism in SIHATSU (Silat Hati Suci): Practices and Impact - Alvi Nour Sholihah (http://jagadalimussirry.com/, 2022)
This article discusses one of the phenomena in Gresik Regency, precisely in Bunga District, there is an internal martial arts college called Sihatsu in which it only teaches three movements starting with